Ultrasonic Sensor-Based Personalized Multichannel Audio Rendering for Multiview Broadcasting Services. (8th April 2013) - Kim, Yong Guk; Moon, Sang-Taeck; Choi, Seung Ho; Kim, Hong Kook
An ultrasonic sensor-based personalized multichannel audio rendering method is proposed for multiview broadcasting services. Multiview broadcasting, a representative next-generation broadcasting technique, renders video image sequences captured by several stereoscopic cameras from different viewpoints. To achieve realistic multiview broadcasting, multichannel audio that is synchronized with a user's viewpoint should be rendered in real time. For this reason, both a real-time person-tracking technique for estimating the user's position and a multichannel audio rendering technique for virtual sound localization are necessary in order to provide realistic audio. Therefore, the proposed method is composed of two parts: a person-tracking method using ultrasonic sensors and a multichannel audio rendering method using MPEG Surround parameters. In order to evaluate the perceptual quality and localization performance of the proposed method, a MUSHRA listening test is conducted, and the directivity patterns are investigated. It is shown from these experiments that the proposed method provides better perceptual quality and localization performance than a conventional multichannel audio rendering method that also uses MPEG Surround parameters.